Preeclampsia and Cardiovascular Disease in a Large UK Pregnancy Cohort of Linked Electronic Health Records: A CALIBER Study. Issue 13 (24th September 2019) - Leon, Lydia J.; McCarthy, Fergus P.; Direk, Kenan; Gonzalez-Izquierdo, Arturo; Prieto-Merino, David; Casas, Juan P.; Chappell, Lucy
Abstract : Background: The associations between pregnancy hypertensive disorders and common cardiovascular disorders have not been investigated at scale in a contemporaneous population. We aimed to investigate the association between preeclampsia, hypertensive disorders of pregnancy, and subsequent diagnosis of 12 different cardiovascular disorders. Methods: We used linked electronic health records from 1997 to 2016 to recreate a UK population-based cohort of 1.3 million women, mean age at delivery 28 years, with nearly 1.9 million completed pregnancies. We used multivariable Cox models to determine the associations between hypertensive disorders of pregnancy, and preeclampsia alone (term and preterm), with 12 cardiovascular disorders in addition to chronic hypertension. We estimated the cumulative incidence of a composite end point of any cardiovascular disorder according to preeclampsia exposure. Results: During the 20-year study period, 18 624 incident cardiovascular disorders were observed, 65% of which had occurred in women under 40 years. Compared to women without hypertension in pregnancy, women who had 1 or more pregnancies affected by preeclampsia had a hazard ratio of 1.9 (95% confidence interval 1.53–2.35) for any stroke, 1.67 (1.54–1.81) for cardiac atherosclerotic events, 1.82 (1.34–2.46) for peripheral events, 2.13 (1.64–2.76) for heart failure, 1.73 (1.38–2.16) for atrial fibrillation, 2.12 (1.49–2.99) for cardiovascular deaths, and 4.47 (4.32–4.62) for chronic hypertension. Differences in cumulative incidence curves, according to preeclampsia status, were apparent within 1 year of the first index pregnancy. Similar patterns of association were observed for hypertensive disorders of pregnancy, while preterm preeclampsia conferred slightly further elevated risks. Conclusions: Hypertensive disorders of pregnancy, including preeclampsia, have a similar pattern of increased risk across all 12 cardiovascular disorders and chronic hypertension, and the impact was evident soon after pregnancy. Hypertensive disorders of pregnancy should be considered as a natural screening tool for cardiovascular events, enabling cardiovascular risk prevention through national initiatives. Abstract : Supplemental Digital Content is available in the text.